A Holter for Parkinson's Disease Motor Symptoms: STAT-On™ - Cabestany, Joan; Bayés, Àngels (River Publishers Series in Biotechnology and Medical Research, 2024)
A new information and communication technology (ICT) has been deployed in the battle against Parkinson's disease, a neurodegenerative disorder that is both progressive and disabling with significant impact on quality of life. This book explains the experience following from the achieved results in the REMPARK project on Parkinson's disease management up to the launch of a new medical product to the European market, STAT-ON™. The new medical device, STAT-ON™ is a real Holter for the motor symptoms associated to PD. It provides objective information about the severity and distribution of PD motor symptoms and their fluctuations in daily life, allowing for an unbiased and correct monitoring of the patient. This real-time remote monitoring solution gives additional information to neurologists, opening up new possibilities for more effective treatment, more accurate control in clinical trials, and for early detection of motor complications. The number of PD patients is continuously rising, adding complexity, especially in the management at the level of public health. It is an incurable disease, with a symptomatic treatment that tries to alleviate the associated symptoms through a correct adjustment of the medication. For this reason, it is also very important to be aware of changes in the manifestation of the symptoms, which may indicate the need for an adjustment or even a change in the therapy strategy. The intensive complementary use of STAT-ON™ by neurologists, health professionals and researchers, will increase the independence and quality of life of patients, improving their disease management, and contributing to a deeper understanding of the nature of the disease.